STRATEGI GURU DALAM MENINGKATKAN KARAKTER RELIGIUS PADA SISWA MELALUI PEMBIASAAN MEMBACA SURAT YAASIIN DI SDN SIMPANG TIGA KOTA CILEGON - Nining Roihatul Jannah; Ujang Jamaludin; Istinganatul Ngulwiyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the teachers’ strategy to improve students’ religious character through reading Yaasiin habituation at grade VA SDN Simpang Tiga. The method of this research was a qualitative method, with a descriptive qualitative type. Data were collected through observation and interview, which were then analyzed by using the Miles and Huberman model. The results of this study revealed that Islamic education teachers at SDN Simpang Tiga improved the students’ religious character through reading Yaasiin habituation. It was found that the teachers were able to carry out the process of improving the students’ religious character through distance learning activities and to know the religious character possessed by students at grade VA SDN Simpang Tiga.